Using Zebrafish to Elucidate Glial-Vascular Interactions During CNS Development - Umans, Robyn A.; Pollock, Carolyn; Mills, William A.; Clark, Kareem C.; Pan, Y. Albert; Sontheimer, Harald (Frontiers in Cell and Developmental Biology, 2021)
An emerging area of interest in Neuroscience is the cellular relationship between glia and blood vessels, as many of the presumptive support roles of glia require an association with the vasculature. These interactions are best studied in vivo and great strides have been made using mice to longitudinally image glial-vascular interactions. However, these methods are cumbersome for developmental studies, which could benefit from a more accessible system. Zebrafish (Danio rerio) are genetically tractable vertebrates, and given their translucency, are readily amenable for daily live imaging studies. We set out to examine whether zebrafish glia have conserved traits with mammalian glia regarding their ability to interact with and maintain the developing brain vasculature. We utilized transgenic zebrafish strains in which oligodendrocyte transcription factor 2 (olig2) and glial fibrillary acidic protein (gfap) identify different glial populations in the zebrafish brain and document their corresponding relationship with brain blood vessels. Our results demonstrate that olig2 and gfap zebrafish glia have distinct lineages and each interact with brain vessels as previously observed in mouse brain. Additionally, we manipulated these relationships through pharmacological and genetic approaches to distinguish the roles of these cell types during blood vessel development. olig2 glia use blood vessels as a pathway during their migration and Wnt signaling inhibition decreases their single-cell vessel co-option. By contrast, the ablation of gfap glia at the beginning of CNS angiogenesis impairs vessel development through a reduction in Vascular endothelial growth factor (Vegf), supporting a role for gfap glia during new brain vessel formation in zebrafish. This data suggests that zebrafish glia, akin to mammalian glia, have different lineages that show diverse interactions with blood vessels, and are a suitable model for elucidating glial-vascular relationships during vertebrate brain development.